PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL ATAS PERMOHONAN MEREK YANG DIAJUKAN DENGAN ITIKAD TIDAK BAIK (Studi Putusan Nomor 1850 K/Pdt.Sus-HKI/2022) - Lestari, Widya Annisa Pudji; Rahmatiar, Yuniar; Abas, Muhamad (Jurnal Ilmiah Advokasi, 2025)
This research examines the form of legal protection of well-known trademarks in Indonesia in the context of disputes filed in “bad faith”, with a case study of Supreme Court Decision Number 1850 K/Pdt.Sus-HKI/2022 between VANS and OTOVANSCLASSIC trademarks. The purpose of the research is to analyze the effectiveness of the application of legal protection under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This research uses a normative juridical approach with descriptive-analytical methods sourced from literature studies and secondary data. The results show that the Supreme Court provides appropriate legal protection to VANS by canceling the registration of the OTOVANSCLASSIC trademark which is considered to have similarities in principal and filed in bad faith. This decision is a form of preventive and repressive protection against infringement of rights to well-known trademarks and reflects fair law enforcement. Keywords: well-known trademark; bad faith; legal protection; essential similarity; trademark dispute